Effect of size and toasting degree of oak chips used for winemaking on the ellagitannin content and on the acutissimin formation. Issue 2 (March 2015) - Le Grottaglie, L.; García-Estévez, I.; Romano, R.; Manzo, N.; Rivas-Gonzalo, J.C.; Alcalde-Eon, C.; Escribano-Bailón, M.T.
Abstract: The effect of size (2 and 8 mm) and toasting degree (light, medium and high) of oak chips on the C-glycosidic ellagitannins composition of model wine solutions has been studied by HPLC-ESI-MS-MS. Furthermore, the effect of the presence of (+)-catechin (50 mg/L and 200 mg/L) in the solution was assessed. Respecting toasting, the levels of ellagitannins were higher and reached earlier when light-toasted chips were used. Regarding chip size, the highest ellagitannin contents were found in the solutions in contact with the smallest oak chips. Nevertheless, the size of oak chips can be crucial depending on the toasting degree: high temperatures or long times of toasting can provoke the ellagitannin degradation from the whole chip if its size is too small. Acutissimins A and B were detected in the solutions containing (+)-catechin. Unlike the levels of acutissimins, the ellagitannin composition was not affected by the concentration of (+)-catechin in the solutions. Highlights: Grandinin and roburin E were the ellagitannins most susceptible to heat treatments. Higher concentration of ellagitannin was reached when the smallest chips were used. Ellagitannin composition was not affected by the concentration of (+)-catechin. The formation of acutissimins is lower when larger oak chips were used.